THE REALIZATIONS OF TEACHING PROFESSION: FOUR INDONESIAN NOVICE ENGLISH TEACHERS' NARRATIVES DURING THE PANDEMIC - Weni, Tabita Melania Mustaka; Yumarnamto, Mateus (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This study explores teacher professional identity (TPI) of novice English teachers in Indonesia by looking at their narratives related to their experiences before and after they entered the profession. The central question leading this inquiry is “What realizations about the profession shape the participants’ TPI?” The data were collected from four participants through emails and follow-up interviews by phone. The data, then, were co-constructed to create coherent narratives of the four novice teachers. Further analysis was conducted by identifying their new realizations and awareness of being English teachers. These realizations about teaching and the profession were discussed in terms of the TPI elements. The findings indicate that realizations about various aspects of TPI of the novice teachers could lead to a better understanding of their professional identity formation before entering the profession, after entering the profession, and at the time of COVID-19 pandemic (2020-2021). The TPI claims in the three stages indicate the complex process of TPI formation and the implications of the process can be the foundation of English teacher education and professional development reform.